Konsep Kerukunan Masyarakat Multikultural Kabupaten Banyuwangi: The Concept of Harmony in the Multicultural Society of Banyuwangi Regency - M. Syamsudini (Fenomena, 2008)
Ethno-religious conflicts in post-reform Indonesia have threatened national integration, yet Banyuwangi demonstrates a unique model of multicultural harmony. This study explores the local wisdom and social mechanisms sustaining inter-ethnic harmony in this multicultural region. Using a qualitative case study approach with phenomenological and sociological methods, data were collected through interviews, observation, and documentation from customary, religious, and youth leaders. Findings reveal that Banyuwangi’s society comprises diverse ethnic groups—Javanese, Madurese, Balinese, Osing, Arab, Chinese, Mandar, and Malay—whose long-term interaction has produced hybrid cultural practices and democratic values manifested in traditions of deliberation (musyawarah), mutual cooperation (gotong royong), equality, and freedom. The study concludes that harmony is maintained through ethical dialogue, transparency, critical self-reflection, and mutual recognition of differences, recommending the institutionalization of multicultural education in local curricula and the strengthening of communal bonds against primordialism. Konflik etno-religius di Indonesia pasca-reformasi telah mengancam integrasi bangsa, namun Banyuwangi menunjukkan model kerukunan multikultural yang unik. Penelitian ini mengeksplorasi kearifan lokal dan mekanisme sosial yang menopang kerukunan antaretnis di wilayah multikultural tersebut. Menggunakan pendekatan kualitatif studi kasus dengan metode fenomenologis dan sosiologis, data dikumpulkan melalui wawancara, observasi, dan dokumentasi dari tokoh adat, agama, dan pemuda. Temuan menunjukkan bahwa masyarakat Banyuwangi terdiri dari beragam etnis—Jawa, Madura, Bali, Osing, Arab, Cina, Mandar, dan Melayu—yang interaksi jangka panjangnya melahirkan praktik budaya hibrid dan nilai-nilai demokrasi yang terwujud dalam tradisi musyawarah, gotong royong, persamaan, dan kebebasan. Penelitian menyimpulkan bahwa kerukunan dipertahankan melalui dialog etis, transparansi, kritik diri, dan pengakuan timbal balik atas perbedaan, dengan merekomendasikan institusionalisasi pendidikan multikultural dalam kurikulum lokal dan penguatan ikatan komunal melawan primordialisme.